The Small World of Investing: Board Connections and Mutual Fund Returns - Cohen, Lauren; Frazzini, Andrea; Malloy, Christopher (Journal of Political Economy, 2008)
Management for helpful comments. We also thank Nick Kennedy, Stephen Wilson, Laura Dutson, Matthew Healey, Meng Ning, Courtney Stone, and Bennett Surajat for excellent research assistance. We are grateful to BoardEx and Linda Cechova for providing firm board data, Morningstar and Annette Larson for providing mutual fund data, and to the Chicago GSB Initiative on Global Markets for financial support. This paper uses social networks to identify information transfer in security markets. We focus on connections between mutual fund managers and corporate board members via shared education networks. We find that portfolio managers place larger bets on firms they are connected to through their network, and perform significantly better on these holdings relative to their non-connected holdings. A replicating portfolio of connected stocks outperforms a replicating portfolio of non-connected stocks by up to 7.8 % per year. Returns are concentrated around corporate news announcements, consistent with mutual fund managers gaining an informational advantage through the education networks. Our results